Developing material forecasting process in a case company - Puroila, Juuso (My University, 2018)
One of the main tasks of the materials management is to guarantee a sufficiently good service level for production to meet customer demand. In practice, this means delivering the materials at the right time in the right place in the right quantities. However, this task is very challenging, especially if material volumes and consumption fluctuations are high. One way to ensure a good service level to production is to forecast the demand for materials. This aims to anticipate and ensure that suppliers of materials and components are able to respond to the material needs of production. The purpose of this study is to develop the material forecasting process in the case company. The aim is to improve the process by developing and implementing a suitable forecasting method and tool for case company's business environment. The theoretical framework of the research is largely based on the scientific literature of forecasting. The theory part also introduces the field and concept of Materials Management. The study is made in a close collaboration with the case company. The research method is case study and research can be characterized as a development study. The research material consists of meetings organized during the study and the statistical data from the case company's ERP system. The study found that the case company's forecasting process was not effective and the forecasts were too much based on history. However, a suitable method and tool were created to enhance the forecasting process as a result of the development project. The method and tool are compatible with the case company's ERP system. The developed method has been put into operation in the company which shows the successful of the development project. However, the study calls continuous monitoring of the reliability of the developed forecasting method.
Keywords: Forecasting; Forecasting method; Forecasting tool; Materials Management; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|